Music Therapy In Reducing Complications In Chronic Kidney Failure Patients During Hemodialysis: A Literature Review - Lutfiasih Rahmawati; Emmi Wahyuni (Indonesian Journal of Nursing and Health Care, 2024)
Background: During the hemodialysis process, patients may experience acute complications due to decreased comfort, both physically and psychologically.Objective: The This literature review aims to determine whether music therapy can reduce complications in chronic kidney failure patients undergoing hemodialysis.Research Method: This literature review study investigates whether music therapy can reduce complications in chronic kidney failure patients undergoing hemodialysis.Results: A total of 49 articles were found, with 6 articles selected after the screening process, and subsequently analyzed in this literature study. Music therapy has been proven to significantly reduce anxiety, pain, and cramps, balance systolic and diastolic blood pressure, improve sleep quality, decrease respiratory rate, and increase oxygen saturation.Conclusion: Music therapy can reduce complications in chronic kidney failure patients undergoing hemodialysis.